PENGEMBANGAN MEDIA MATHCHESS BERBASIS ANDROID UNTUK MENGATASI PERMASALAHAN PERKALIAN SISWA KELAS IV UPT SPF SDN 106828 SUMBEREJO - Khaissuledi Qawiy; Abdul Mujib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low learning outcomes of students in multiplication material in grade IV UPT SPF SDN 106828 Sumberejo, where 60% of students obtained scores below the KKM (70). Conventional mathematics learning and the lack of interesting learning media cause students to experience difficulties in understanding multiplication concepts and memorizing multiplication tables. The purpose of this study is to develop a valid, practical, and effective Android-based Mathchess learning media to overcome the multiplication problems of grade IV students. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 26 grade IV students of UPT SPF SDN 106828 Sumberejo. Data collection techniques used expert validation sheets, student response questionnaires, and learning outcome tests. Data were analyzed descriptively quantitatively to determine the level of validity, practicality, and effectiveness of the learning media. The results of a field trial involving 26 fourth-grade students of UPT SPF SDN 106828 Sumberejo showed the effectiveness of Mathchess media in improving students' multiplication skills. The trial data showed that students experienced a significant increase in mastery of multiplication material. A total of six students achieved the highest score of 87-90 with the ability to master multiplication up to number 9, ten students obtained a score of 80-86 with mastery of multiplication up to number 7, five students with a score of 77 were able to master multiplication up to number 6, and five students with a score of 70 mastered multiplication up to number 5. The average overall score of students reached 79.54, Based on the results of research and discussion on the development of Android-based Mathchess media to overcome the multiplication problems of fourth-grade students of UPT SPF SDN 106828 Sumberejo. The Mathchess learning media was declared valid and suitable for use based on validation results from material experts (81% - suitable), media experts (62% - suitable), and education practitioners (56.25% - quite suitable), with an average suitability of 66.42%. Keywords: Learning Media, Mathchess, Android